PENGELOLAN PEMBELAJARAN PKn MELALUI MODEL ROLE PLAYING DI SMK - Varianita Varianita (Manajer Pendididikan, 2015)
Some issues in the teaching of citizenship education, among others: 1) lack of positive activities for student learning, 2) lack of student learning outcomes, 3) in response to the lack ofactive student learning, 4) lack of teachers in varying methods and media, 5) learning is still dominated by the teacher. The purpose of this study is: to improve teaching and learning activitiesand outcomes of citizenship education class vocational high school through model role playing. Conclusions this study is the first to increased student learning activities. Both an increase instudent learning outcomes.Keywords: role playing, activities, learning outcomes